Defects in SiC for Quantum Computing. (2019) - Choudhary, Renu; Biswas, Rana; Pan, Bicai; Paudyal, Durga
Abstract: Many novel materials are being actively considered for quantum information science and for realizing high-performance qubit operation at room temperature. It is known that deep defects in wide-band gap semiconductors can have spin states and long coherence times suitable for qubit operation. We theoretically investigate from ab-initio density functional theory (DFT) that the defect states in the hexagonal silicon carbide (4H-SiC) are potential qubit materials. The DFT supercell calculations were performed with the local-orbital and pseudopotential methods including hybrid exchange-correlation functionals. Di-vacancies in SiC supercells yielded defect levels in the gap consisting of closely spaced doublet just above the valence band edge, and higher levels in the band gap. The divacancy with a spin state of 1 is charge neutral. The divacancy is characterized by C-dangling bonds and a Si-dangling bonds. Jahn-teller distortions and formation energies as a function of the Fermi level and single photon interactions with these defect levels will be discussed. In contrast, the anti-site defects where C, Si are interchanged have high formation energies of 5.4 eV and have just a single shallow defect level close to the valence band edge, with no spin. We will compare results including the defect levels from both the electronic structure approaches.